Fast, accurate, and cost-effective poultry sex genotyping using real-time polymerase chain reaction - Cordeiro, Ciro D.; Gonceer, Nesim; Dorus, Steve; Crill, James E.; Moshayoff, Vardit; Lachman, Amit; Moran, Asaf; Vilenchik, Dan; Fedida-Metula, Shlomit (Frontiers in Veterinary Science, 2023)
According to The Organization for Economic Co-operation and Development (OECD), demand for poultry meat and eggs consumption is growing consistently since poultry meat and eggs are readily available and cheap source for nutritional protein. As such, there is pressing demand from industry for improved protocols to determine chicken sex, especially in layer industry since only females can lay eggs. Extensive efforts are being dedicated to avoiding male chicks culling by developing in-ovo sexing detection methods. Any established in-ovo detection method will need to be validated by embryo genotyping. Therefore, there is a growing demand for fast, inexpensive, and precise method for proper discrimination between males and females in the poultry science community. Our aim with this study was to develop an accurate, high-throughput protocol for sex determination using small volumes of blood. We designed primers targeting the Hint-W gene within the W chromosome clearly distinguishing between males and females. In the interest of establishing an efficient protocol without the need for gel electrophoresis, crude DNA extraction without further purification was coupled with qPCR. We validated the accuracy of our method using established protocols and gonad phenotyping and tested our protocol with four different chicken breeds, day-nine embryos, day-old chicks and adult chicken. In summary, we developed a fast, cost-effective, and accurate method for the genotyping of sex chromosomes in chicken.